Effects of Integrative Thai and Alternative Medicine Rehabilitative Program on Motor Power and Activity Daily Living in Stroke Patients - Chanpen, Orarat; Leaungsomnapa, Yosapon; Vasanat, Panee; Anusasanarak, Sucheera; Boonta, Natthajanya; Khamdaengyodtai, Yenpat; Prangsaowapha, Kankhanin; Prasertsri, Nusara (Journal of Phrapokklao Nursing College, Chanthaburi, 2018)
This quasi-experimental, one group, pre-test/post-test, prospective study was designed to determine the effect of the integrative between Thai alternative medicine and alternative medicine program on patients’ motor power and activities of daily living (ADL) function. Participants were 25 stroke patients who were treated at Sakaeo Crown Prince Hospital and permitted discharge. Measures included demographic data, motor power assessment scale and Barthel Index–ADL (Thai version), reliability was test (Cronbach’s alpha = .96). The intervention was conducted from October 2014 to July 2015. Data were analyzed using frequency, percentage, mean, standard deviation, median, one group repeated measure ANOVA, and multiple comparison by Bonferroni method. The research found that motor power mean scores at 1 month, 2 months, and 3 months after received intervention were significantly differences (MD = 1.16, p < .001; MD = 2.08, p < .001, and MD = 2.52, p < .001, respectively). The mean score of motor power after received intervention at 2 and 3 months was significantly higher than at 1 month (MD = .92, p < .01, and MD = 1.36, p < .001, respectively), and the mean score of motor power after received intervention at 3 months was significantly higher than at 2 months (MD = .44, p < .001). The ADL mean scores at 1 month, 2 months, and 3 months after received intervention were significantly differences (MD = 49.20, p < .001; MD = 57.20, p < .001, and MD = 62.32, p < .001, respectively). The ADL mean scores after received intervention at 2 and 3 months was significantly higher than at 1 month (MD = 7.96, p < .001, and MD = 13.08, p < .001, respectively), and the ADL mean scores after received intervention at 3 months was significantly higher than at 2 months (MD = 5.12, p < .01). This research findings suggest that should take the program as the option to providing rehabilitation services for stroke patients in hospital that availability of integrative Thai and alternative medicine.